Age at menarche and depressive symptoms in older Southern Chinese women: A Mendelian randomization study in the Guangzhou Biobank Cohort Study. (January 2018) - Au Yeung, Shiu Lun; Jiang, Chaoqiang; Cheng, Kar Keung; Xu, Lin; Zhang, Weisen; Lam, Tai Hing; Leung, Gabriel Matthew; Schooling, C. Mary
Abstract: To clarify the causal role of age at menarche in depressive symptoms we conducted a Mendelian randomization study using a large Southern Chinese cohort ( n = 12, 233). A genetic allele score was derived using stepwise regression with cross validation. Older age at menarche was not associated with geriatric depression scale score. Our findings suggest that higher rates of depression in women are likely attributable to other factors which require investigation. Highlights: Mendelian randomization (MR) study is more resistant to confounding. This MR study showed menarche unrelated to depressive symptoms. Larger MR studies would be necessary to verify our findings.